2009
DOI: 10.1590/s2236-89062009000200007
|View full text |Cite
|
Sign up to set email alerts
|

Trilhas afetam comunidades arbóreas florestais?: dois levantamentos na Floresta Atlântica do sudeste brasileiro

Abstract: -(Do trails affect forest tree communities? Two surveys in the Atlantic Forest of southeastern Brazil). Forest trails can infl uence the composition and structure of plant communities by causing abiotic changes along their course and in the vicinity. To understand the behavior of the fl oristic and structural vegetation along the trails, two surveys were conducted in the Atlantic Forest of southeastern Brazil, in the "Parque Estadual das Fontes do Ipiranga", São Paulo, State of São Paulo, and in the "Mata da B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
0
5
0
7
Order By: Relevance
“…However, the situation in the case of a trail is a little different, since the people and animals that use it can transport seedlings to that region and, as a consequence, this area could have conditions to carry on with the natural succession. Nevertheless, it seems therefore that in the trail vicinity and in the forest interior the arrival of seedlings is similar (Eisenlohr et al 2009). Some researches carried out in trails and its surroundings have indicated higher rates of germination in soils with higher contents of organic matter and nutrients (e.g., Cole & Spildie 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the situation in the case of a trail is a little different, since the people and animals that use it can transport seedlings to that region and, as a consequence, this area could have conditions to carry on with the natural succession. Nevertheless, it seems therefore that in the trail vicinity and in the forest interior the arrival of seedlings is similar (Eisenlohr et al 2009). Some researches carried out in trails and its surroundings have indicated higher rates of germination in soils with higher contents of organic matter and nutrients (e.g., Cole & Spildie 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Researches has shown that the "trail effect" (as we will call this effect) determines a strong physical impact on soil and vegetation (Cole 1978, Roovers et al 2004, possibly causing alterations, for example, in the seed germination (Comita & Goldsmith 2008), in the floristic diversity (Roovers et al 2004) and in the structure of woody plant communities (Eisenlohr et al 2009). Information regarding the susceptibility of the vegetation to changes caused by the construction and use of natural trails must therefore become available to the planners responsible for the routing and installation of new trails.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentre os poucos estudos feitos nesse sentido para a Mata Atlântica, foi verificado que um trecho de mata de São Paulo (o mesmo do presente estudo) e outro trecho em Viçosa-MG apresentaram algumas variações estruturais possivelmente relacionadas ao tipo de impacto causado por trilhas (Eisenlohr et al 2009). Além de modificações na estrutura da vegetação nas bordas das trilhas, a luminosidade e a força dos ventos, potencialmente modificadas pela abertura da trilha, aliadas a impactos físicos por pisoteio (Roncero-Siles 2003, Roovers et al 2004), podem resultar em uma ainda não mensurada alteração nos padrões florísticos em comunidades florestais atlânticas.…”
Section: Introductionunclassified
“…Trilhas podem causar modificações em seu ambiente de ocorrência e nas áreas florestais adjacentes (Cole 1978). Os estudos sobre trilhas trataram, de maneira geral, dos impactos do uso, elencando seus efeitos como sendo diretos, tais como destruição da cobertura vegetal, diminuição da diversidade de espécies, redução da altura e vigor da floresta; e indiretos, tais como mudança na composição das espécies, estrutura da comunidade, perda do microclima, compactação e aceleração da erosão do solo, além de distúrbios da fauna (Cole 1978, Kuss 1986, Boucher et al 1991, Magro 1999, Koehler et al 2000, Leung & Marion 2000, Newman et al 2003, Lechner 2006, Villagra 2008, Eisenlohr et al 2009, Hirata et al 2010.…”
Section: Introductionunclassified